High stability and robustness of a developed novel laser acupuncture theranostic device. (November 2017) - Zhong, Fulin; Kong, Zhenglun; Xu, Guoyi; Li, Ting
Abstract: Recently, acupuncture, traditional to Chinese medicine for dozens of centuries, has been receiving recognition as a well-established and widely-cherished methodology among the newly-discovered diagnoses. It is currently embracing an ever-growing and wide-spreading global popularity. However, in comparison with traditional acupuncture utilizing metallic needles, laser acupuncture nevertheless stands out as a non-invasive, painless approach to diseases, eliminating the risk of infection. Due to the advantages of laser acupuncture, we innovatively developed a portable theranostic device adopting laser acupuncture. In our study, a series of experiments were performed to substantiate as well as improve the robustness and stability of this device for future clinical trials. For instance, we adopted a type of pluggable interface designed to improve the stability of laser diode part. In addition, we measured the dark noise of every channel for data interpretation. The results have quantitatively demonstrated the device's great potentiality and reliability in clinical treatments. In future, the device will be tested in noninvasive theranostic clinic trials to fully test the capabilities of treating various diseases. Highlights: Innovatively developed portable laser acupuncture theranostic device. High Robustness acupuncture theranostic electronic module and improved stability of laser accupuncture module. A series of experiments conducted to verify the robustness and stability of this device.